Diaphragmatic eventration mimicking congenital diaphragmatic hernia: The value of chest radiograph and barium meal in diagnosis - Saleh, Mohammed; Suwaid, Mohammad; Idris, Sule; Tabari, Abdulkadir; Isyaku, Kabiru (Nigerian Journal of Basic and Clinical Sciences, 2026)
A 6-month-old boy was referred to the radiology department of the Aminu Kano Teaching Hospital for chest X-ray, from the Emergency Pediatric unit of the Hospital, on account of severe bronchopneumonia in association with diaphragmatic hernia to rule out pulmonary tuberculosis, but for which, chest X-ray and a complimentary urgent Barium meal studies showed a complete left-sided eventration of the hemidiaphragm. He had successful plication of the left hemidiaphragm and the bowel loops, and spleen were carefully freed and fixed back into the abdomen. The paper highlighted on the key role played by the chest X-ray and an immediate complimentary upper gastrointestinal barium studies in making the diagnosis of this life-threatening condition in a resource-poor environment. The relevant literature was also reviewed.